Distribution and reproduction of Procambarus clarkii in relation to water management, salinity and habitat type in the Camargue. Issue 3 (17th October 2013) - Meineri, Eric; Rodriguez‐Perez, Hector; Hilaire, Samuel; Mesleard, François
ABSTRACT Procambarus clarkii, one of the most invasive aquatic species worldwide, is present in Mediterranean estuarine regions. Water management of these deltas involves massive freshwater inputs, reducing wetland salinity and altering natural flooding periods, two important factors for P. clarkii. The paper examines whether water management affects the distribution and reproduction success of P. clarkii in Mediterranean estuarine regions. Procambarus clarkii was sampled in the Camargue every 6 weeks throughout a whole year. Forty‐eight stations were sampled to represent the available habitats and water management types in the study region: temporary ponds, semi‐permanent marshes, permanent marshes, canals and ricefields. Salinity and habitat effects on capture probability, abundance and proportion of juveniles were explored within each season to study species distribution, to identify suitable habitats for reproduction and its timing, and to assess how salinity affects these traits. Only a few crayfish were found above 10 g L–1 salinity and a few juveniles were found above 5 g L–1. Procambarus clarkii was found in the five habitat types sampled but with lower capture probability and abundance in ricefields and canals. The proportion of juveniles was highest in temporary ponds during their seasonal peak. These results suggest that low salinity increases the occurrence, the abundance and the reproduction success of P. clarkii but that hydroperiod length per se does not affect P. clarkii. Furthermore, the results suggest that temporary water bodies within the salinity range of the species are used as safe sites for reproduction. A significant reduction of freshwater inputs into estuarine ecosystems is needed to restore a higher salinity level and to reduce the reproductive success and expansion of P. clarkii. Copyright © 2013 John Wiley & Sons, Ltd.